HUBUNGAN LAMA PENGGUNAAN OBAT ARV TERHADAP KADAR HEMOGLOBIN PADA PENDERITA HIV/AIDS DI POLI VCT RSUD PROF. DR. SOEKANDAR KABUPATEN MOJOKERTO - Indah Lestari; Emyk Windartik; Gendewa Goa Wijaya (Bahasa Indonesia, 2016)
Antiretroviral (ARV) therapy was undertaken with HIV/AIDS by took medication for life, to suppress the amount of virus. Most people took antiretroviral (ARV) drugs had some side effects, one of which decreased in hemoglobin (Hb), which was influenced by factors duration of therapy and CD4 levels. As a result of long use of antiretroviral (ARV) drugs by the side effects that cause a decrease in hemoglobin. The research objective was to determine the relationship of long used of ARV (Antiretroviral) on levels of hemoglobin in people with HIV / AIDS. The research design corelation analytical with cross sectional approach. Entired population HIV/AIDS patients undergoing antiretroviral therapy in Polyclinic VCT at Prof. Dr. Soekandar Hospital District Mojokerto regency as many as 65 respondents. Samples of 25 respondents took by purposive sampling. Old data retrieval use of ARV drugs by used observations of medical records and hemoglobin concentration used check tool hemoglobin (Hb Quick Chek) and secondary data. Test data analysis using the Spearman rho shows ρ (0.002) < α (0.05), it means that there is a long-standing relationship to the use of ARV drugs hemoglobin levels. Decreases in hemoglobin may occur due to antiretroviral drugs tend to inhibit the enzyme reverse transcriptase and cause damage to the spinal cord so that hemoglobin in the blood is very low which leads to anemia. One way to suppress the occurrence of side effects can be done by taking supplements that can increase the levels of hemoglobin in the blood.